Conflicts and Challenges of Truth-Telling in Dentistry: A Case-Based Ethical Analysis - Azam Khorshidian; Ehsan Shamsi Gooshki; Alireza Parsapoor (Tehran University of Medical Sciences, 2022)
Objectives: The basis of truth-telling is respecting the autonomy of patients and developing an ability to make informed decisions with valid consent. The purpose of this study was to ethically analyze the conflicts about truth-telling in dentistry. Materials and Methods: This case analysis focused on the issues of truth-telling in medicine and dentistry. The challenges encountered by dentists with respect to ethical issues related to truth-telling were discussed and analyzed by the research team. Results:  The literature review showed that the issue of truth-telling in dentistry has been addressed from three aspects: Truth-telling about other dentists' medical errors, truth-telling about dangerous, refractory, or incurable diseases, and truth-telling to children or incompetent individuals for decision-making. Conclusion: When the duty of the dentist in truth-telling is conflicted with some other moral obligations, the conflict between the prima facie duties arises. The principle-based ethical theories provide a suitable conceptual framework for moral judgement in such conflicts. In cases of conflicts related to truth-telling, a balance should be maintained between principles and rules such as fidelity, respect for autonomy, maintaining trust in dentist-patient relation, and best interest of patients. The decision in truth-telling should be made individually for each patient based on the specific contextual conditions.